A rare case of typhoid presenting with fever, ascites, hyponatremia, thrombocytopenia, mesenteric lymphadenitis, and multi-drug resistance - A Priya Margaret; P John Solomon; Harita Lohith (Wolters Kluwer Medknow Publications, 2015)
A rare case of typhoid presenting with thrombocytopenia, hyponatremia, ascites mesenteric adenitis, and multi-drug resistance is being presented in this article. An 8-year-old girl was admitted with a history of fever, vomiting, abdominal pain and loose stools. Clinical examination revealed fever and hepatosplenomegaly. Investigations showed leucopenia, thrombocytopenia and hyponatremia. Blood Widal was positive, and blood culture grew Salmonella typhi. Ultrasound abdomen revealed ascites, hepatosplenomegaly, mesenteric lymphadenopathy and thickening of the gall bladder. She was treated with ciprofloxacin intravenously for 6 days and when the fever persisted injection ceftriaxone was added. Ciprofloxacin was given intravenously for a total of 15 days and injection ceftriaxone was given for 12 days. Even then, the fever persisted and hence oral azithromycin was added. Fever subsided completely in 3 days with azithromycin and she became asymptomatic without fever, loose stools, abdominal pain or anything on follow-up after 3 months.